2005
DOI: 10.1136/bjo.2004.058057
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of intraocular pressure in healthy Iranian individuals: the Tehran Eye Study

Abstract: Aim: To provide data on the distribution of intraocular pressure (IOP) in an Iranian population. Methods: Through a population based, cross sectional study, 4565 Tehran citizens were studied in the Tehran Eye Study. The findings from the participants (n = 3834) aged 10 years and older free of glaucoma diagnosis or suspicion who had undergone applanation tonometry examination are presented. All participants received a standardised protocol including applanation tonometry, fundus examination, demographic data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 36 publications
9
55
3
Order By: Relevance
“…11,12 Schulzer and Drance found that adjustment for systolic blood pressure accounted for any age effect. 13 Consistent associations with increasing IOP have been reported for increasing systolic blood pressure, 5,7,8,10,12,16,17 darker iris color, 9,14,18 and myopia. 6,14,18 Once glaucoma is diagnosed and treatment is initiated, the influence on IOP attributable to demographic, systemic, and ocular factors might be overwhelmed by the impact of glaucoma treatment.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…11,12 Schulzer and Drance found that adjustment for systolic blood pressure accounted for any age effect. 13 Consistent associations with increasing IOP have been reported for increasing systolic blood pressure, 5,7,8,10,12,16,17 darker iris color, 9,14,18 and myopia. 6,14,18 Once glaucoma is diagnosed and treatment is initiated, the influence on IOP attributable to demographic, systemic, and ocular factors might be overwhelmed by the impact of glaucoma treatment.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3] Studies of factors that influence IOP have been conducted in large populations consisting mostly of people without glaucoma. Increasing age has been associated with increasing IOP in most studies, [4][5][6][7][8][9][10] although decreasing IOP with increasing age has been reported in two studies of Asian populations. 11,12 Schulzer and Drance found that adjustment for systolic blood pressure accounted for any age effect.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have attempted to identify risk factors associated with higher IOP (Armaly 1967;Colton & Ederer 1980;Klein & Klein 1981;Shiose 1984Shiose , 1990David et al 1987;Shiose et al 1991;Sommer et al 1991;Klein et al 1992;Leske et al 1997;Bonomi et al 1998;Nomura et al 1999Nomura et al , 2002Nomura et al , 2004Mori et al 2000;Hashemi et al 2005;Lin et al 2005;Mitchell et al 2005;Nakano et al 2005;Xu et al 2005;Suzuki et al 2006). It is well known that IOP increases with age ) the other important risk factor for glaucoma ) among Black, White and Iranian populations (Armaly 1967;Colton & Ederer 1980;Klein & Klein 1981;David et al 1987;Klein et al 1992; Leske et al 1997;Bonomi et al 1998;Hashemi et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the mean sertraline dose was 95±2.5 mg daily. Previous studies have revealed (2,17,27,29,31)that the occurrence of this effect depends on the drug plasma level and its metabolites,occurring at a mean daily dose of SSRIs exceeding 20 mg(31) or ≄1 defined daily dose (17). In this study, we evaluated the effect of sertraline on the level of IOP and CDR in patients with anxiety disorders, mixed anxiety and depressive disorder, major depressive disorder.…”
Section: Pharm Biomed Res 2017; 3(3): 36mentioning
confidence: 98%